An empirical investigation of the economic payoffs of e-business and CRM innovations. (9th November 2004) - Shin, Namchul
While the question of the benefits of e-business initiatives has been an issue in both the academic and business worlds, there has been little empirical research on the value created from such initiatives. Using Information Week's annual data set of innovative IT users, this study empirically examines the contribution of e-business initiatives to firm performance, measured by gross margin, revenue per employee, ROA, and ROE. The measure of e-business initiatives is constructed by combining e-business and CRM innovations. Data are analysed for the full sample and for both the manufacturing and service industry sectors for the 2 years of 1999 and 2000. The results show that e-business and CRM innovations contribute to firm performance significantly. The results indicate that when firms deploy e-business technologies and practices early and creatively, namely when their e-business initiatives are innovative, they can generate significant economic returns.